THE IMPACT OF TRANSLATION TOOLS TOWARDS STUDENT TRANSLATORS’ SKILLS - Omolu, Fikriani Aminun; Mappewali, A. (Premise: Journal of English Education and Applied Linguistics, 2024)
Technological advances have created translation tools as part of translation technology, which is widely used by the public and academics, including students. On the one hand, students accept the existence of translation technology positively as it provides easiness for them to do their coursework. This research aimed to discover the impact of translation technology on students' translation skills. The result of this study is a recommendation for translation course lecturers to suggest that students utilize translation technology. The participants of this study were 25 students of the English Education Study Program of Universitas Muhammadiyah Palu. They were selected by using a total sampling technique. The data found indicates that a constant of 39.234 shows that students' Translation Skills are worth 39.234 without using Translation Technology. The regression coefficient of 0.794 indicates that each increase in Translation Technology use will increase Translation Skills by 0.794. The results of this study signify that translation technology does not significantly impact students' translation skills. The probability number is 0.103, which is greater than 0.05. Consequently, the H0 is accepted, or there is no significant influence of Translation Technology on the Translation Skills of student translators. The study implies that technology tool is a secondary aspect of promoting translating skills.